Towards personalised rapid label free miRNA detection for cancer and liver injury diagnostics in cell lysates and blood based samples. Issue 26 (27th June 2018) - Duffy, James; Padovani, Francesco; Brunetti, Giulio; Noy, Peter; Certa, Ulrich; Hegner, Martin
Abstract : Label free nanomechanical miRNA detection from biological samples utilising cantilever arrays in an automated diagnostic platform. Abstract : Advances in prevention, diagnosis and therapy are coupled to innovation and development of new medical tools, leading to improved patient prognosis. We developed an automatic biosensor platform that could provide a non-invasive, rapid and personalised diagnosis using nanomechanical cantilever sensors. miRNA are involved in gene expression and are extractable biomarkers for multiple diseases. We detected specific expression patterns of miRNA relevant to cancer and adverse drug effects directly in cell lysates or blood based samples using only a few microliters of sample within one hour. Specific miRNA hybridisation to the upper cantilever surface induces physical bending of the sensor which is detected by monitoring the position of a laser that reflects from the sensors surface. Internal reference sensors negate environmental and nonspecific effects. We showed that the sensitivity of label free cantilever nanomechanical sensing of miRNA surpasses that of surface plasmon resonance by more than three orders of magnitude. A cancer associated miRNA expression profile from cell lysates and one associated with hepatocytes derived from necrotic liver tissue in blood-based samples has been successfully detected. Our label free mechanical approach displays the capability to perform in relevant clinical samples while also obtaining comparable results to PCR based techniques. Without the need to individually extend, amplify or label each target allowing multitarget analysis from one sample.